Orally administered Bi2S3@SiO2 core-shell nanomaterials as gastrointestinal contrast agents and their influence on gut microbiota. (January 2022) - Chen, Rui; Zhou, Ruyi; Qiao, Jiyan; Yang, Yanan; Zhou, Xingfan; Bai, Ru; Wang, Yuqian; Yan, Liang; Wu, Chongming
Abstract: Effective and safe contrast agents for X-ray computed tomography (CT) imaging of the gastrointestinal (GI) tract are quite desirable for realizing high diagnostic accuracy and low toxicity in the clinic. Herein, we synthesize a series of silica-coated bismuth sulfide core-shell nanomaterials (Bi2 S3 @SiO2 ) of various sizes and systematically study their GI CT contrast performance and potential toxic effects in comparison with those of barium sulfate (BaSO4 ) in mice. The in vivo experimental results suggest that these Bi2 S3 @SiO2 core-shell nanomaterials display superior CT contrast performance and higher elimination efficacy than BaSO4 by single-dose exposure manner (10 ​mg/kg Bi element/b.w. for Bi2 S3 @SiO2 versus 30 ​mg/kg Ba element/b.w. for BaSO4 ). Furthermore, 28 days after exposure, Bi2 S3 @SiO2 core-shell nanomaterials show minimal toxic effects in vivo and nonsignificant influences on the structure and function of the gut microbiota in mice. This demonstrates that no adverse effects on the gut homeostasis are induced by Bi2 S3 @SiO2 core-shell nanomaterials and, thus, suggests that they can act as excellent and safe CT contrast agents for GI tract imaging. Graphical abstract: We prepared a serious of Bi2 S3 @SiO2 core-shell nanostructures with different sizes and then investigated their gastrointestinal contrast ability and potential toxic effects in comparison to clinical used barium sulfate, in particular homeostasis of the gut microbiota. Image 1